Optimization Process Production Sorbitol Through MnCuFe2O4 Photonanocatalysis - Krisnayana, Rina; Nugroho, Gunawan; Biyanto, Totok Ruki (Journal of Ecohumanism, 2024)
Indonesia have a lot of biomassa is rice straw. The largest content rice straw is cellulose. Cellulose can be converted into sorbitol. The sorbitol produced is useful for various industries are chemical industry, textiles, cleaning, dust control, packaging, agriculture and fuel. In this study, we produced sorbitol from rice straw using multistage is NaOH hydrolysis followed by MnCuFe2O4 photonanocatalysis. The aim this study is maximize yield sorbitol, with the novelty of using photonanocatalysts MnCuFe2O4. This study provides results that by using multistage is NaOH hydrolysis followed by MnCuFe2O4 photonanocatalysis, sorbitol was successfully obtained from rice straw. The yield sorbitol model in this process is in the form of 2FI (two interaction factors). Optimization using RSM (Response Surface Methodology), genetic algorithm and PSO methods. The optimum yield sorbitol is at UV light power = 125 W and exposure time of 60 minutes. Morphological characterization by scanning electron microscope (SEM) shows granular sorbitol. FTIR shows that sorbitol has characteristics of alcohol (-OH) and alkyl (-CH) functional groups. X-ray diffraction (XRD) give the resulting sorbitol is amorphous sorbitol. Thermogravimetric analysis (TGA) shows that the weight % degrades with increasing temperature, where sorbitol begins to degrade at a temperature of 200⁰C and a maximum at a temperature of 357⁰C.